Management of Enamel Defects with Resin Infiltration Techniques: Two Years Follow Up Retrospective Study - Alessia Vincenza Brescia; Lorenzo Montesani; Dimitri Fusaroli; Raffaella Docimo; Gianfranco Di Gennaro (MDPI AG, 2022)
Background: Developmental Defects of Enamel (DDE) represent an aesthetic, functional, and often psychological problem, especially in young patients. Infiltrative treatment with resin (Icon-DMG, Hamburg, Germany) is a minimally invasive technique based on the infiltration of high viscosity resin inside the hypomineralized enamel, modifying its optical properties. The aim of this paper is to evaluate the clinical efficacy of superficial infiltration in the treatment of white enamel defects of the anterior sector with pre-eruptive etiology and its stability over time. Methods: Thirty-three patients affected by DDE associated with mild and moderate Molar Incisor Hypomineralization (MIH), mild and moderate fluorosis, and post-traumatic hypomineralization treated with resin infiltration were retrospectively retrieved. Results: In all cases an improvement in aesthetic appearance was achieved, and the 24-month follow-up confirmed the stability of the results. However, in the cases of traumatic hypomineralization the results were not completely satisfactory. Conclusions: The superficial infiltration technique can be considered a valid minimally invasive alternative to traditional treatment of mild or moderate fluorosis and mild MIH.